DETERMINANTS OF SMALL MEDIUM BUSINESS UNDERSTANDING OF MICRO, SMALL AND MEDIUM ENTITIES FINANCIAL ACCOUNTING STANDARDS - Mei Susi Setyo Wati; Desrir Miftah; Julina Julina (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The purpose of the study was to determine the effect of education level, educational background, business scale, business age and information & socialization on the understanding of Small and Medium Enterprises (SMEs) in preparing financial reports based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in District of Kepenuhan Hulu, Rokan Hulu, Riau. The research population is 88 SMEs from various sectors that have been registered with the Cooperatives and SMEs Office in Kepenuhan Hulu District. The sampling technique used was total sampling. The type of data used is primary data, which is obtained by distributing questionnaires directly to respondents. The data analysis technique used is multiple linear regression analysis. The results showed that the level of education of business actors did not affect understanding in the preparation of financial statements based on SAK EMKM. Educational background has a significant positive effect on the understanding of SMEs in preparing financial reports based on SAK EMKM. The scale of business does not affect the understanding of SMEs in preparing financial reports based on SAK EMKM. Age of business does not affect the understanding of SMEs in preparing financial reports based on SAK EMKM. Information and socialization have a significant positive effect on the understanding of SMEs in preparing financial reports based on SAK EMKM.